2015
DOI: 10.1159/000440972
|View full text |Cite
|
Sign up to set email alerts
|

Ionized Magnesium and Regional Citrate Anticoagulation for Continuous Renal Replacement Therapy

Abstract: Background: The regional citrate anticoagulation (RCA) induces changes in total (Catot) and ionized (Ca2+) calcium. As of now, we do not have much information about parallel changes of total (Mgtot) and ionized (Mg2+) magnesium. Methods: The authors compared changes of Mg2+ and Mgtot with changes of Ca2+ and Catot in 32 critically ill patients on 4% trisodium citrate (4% TSC) with calcium-free fluids. Results: The median co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Brain found a significantly negative magnesium balance using dialysis/replacement fluids containing 0.5 mmol Mg tot per liter [ 7 ]. In our previous research on ionised magnesium we found similar negative magnesium balance when using fluids with 0.75 mmol/l Mg tot per liter [ 9 ]. With regards to rather difficult assessment of magnesium deficit in critically ill RCA may lead to inapparent losses of magnesium and depletion of its relatively low body pool [ 6 , 8 , 18 ].…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Brain found a significantly negative magnesium balance using dialysis/replacement fluids containing 0.5 mmol Mg tot per liter [ 7 ]. In our previous research on ionised magnesium we found similar negative magnesium balance when using fluids with 0.75 mmol/l Mg tot per liter [ 9 ]. With regards to rather difficult assessment of magnesium deficit in critically ill RCA may lead to inapparent losses of magnesium and depletion of its relatively low body pool [ 6 , 8 , 18 ].…”
Section: Introductionmentioning
confidence: 67%
“…The daily magnesium substitution is a matter of debate with regards to reported deficit of intracellular magnesium in general population and in intensive care patients in particular [ 4 8 ]. Thus CRRT in ICU frequently requires early magnesium substitution and the requirements are further increased with regional citrate anticoagulation (RCA)[ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to hypomagnesaemia if magnesium replenishment with the substitution uid is not adequate. It was observed that post-lter magnesium concentrations decrease in a manner similar to the concentrations of calcium ions under RCA [24]. When using substitution uid containing 0.5 mmol/L magnesium, a tendency towards a decreased magnesium concentration was observed during haemo ltration treatment.…”
Section: Magnesiummentioning
confidence: 79%
“…Second, this study was limited to a single center with a single CRRT machine and filter; the effect of different CRRT machines and filters on the extracorporeal removal of n-Ca is unclear. Third, the optimized calcium DOI: 10.1159/000494693 supplementation approach did not consider the effect of RCA on bone metabolism and magnesium metabolism for patients receiving long-term RCA-CRRT [24][25][26].…”
Section: Discussionmentioning
confidence: 99%